The Effect of Collage Activities on Fine Motor Skills of Children Aged 5-6 Years at PAUD Harapan Ummat Academic Year 2022/2023 - Fanny Ariyanti; Suri Handayani Damanik (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine and obtain empirical data about the effect of collage activities on the fine motor skills of children aged 5-6 years. Research conducted at the PAUD Harapan Ummat. The method used in this study is quantitative research (experimental), the type of research is Pre-Experimental Designs, with the form of One-Group Pretest-Posttest Design. The population in this study were children aged 5-6 years at PAUD Harapan Umat Tahun. The research sample was taken using a random sampling technique for children aged 5-6 years at PAUD Harapan Umat with details of 14 boys and 6 girls. A total of 20 children. Based on the results of the hypothesis test through the calculations, the calculated T value is smaller, namely 11 compared to the T table value = 52 (where α = 0.025 and n = 20). In order to obtain Tcount <Ttable or 11 <52, so that H0 is rejected and H1 is accepted. So, it can be concluded from the hypothesis that: